If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 4 = -4x + -17 Reorder the terms: 4 + -7x = -4x + -17 Reorder the terms: 4 + -7x = -17 + -4x Solving 4 + -7x = -17 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 4 + -7x + 4x = -17 + -4x + 4x Combine like terms: -7x + 4x = -3x 4 + -3x = -17 + -4x + 4x Combine like terms: -4x + 4x = 0 4 + -3x = -17 + 0 4 + -3x = -17 Add '-4' to each side of the equation. 4 + -4 + -3x = -17 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = -17 + -4 -3x = -17 + -4 Combine like terms: -17 + -4 = -21 -3x = -21 Divide each side by '-3'. x = 7 Simplifying x = 7
| x^3+8x-30=0 | | 6y+2(y+5)=12 | | B=870(1+0.03)9+9+9+9+9+9+9+9+9 | | q(15)=100-4*15 | | -6x-26=-12x+58 | | 6x+3x=8x-5 | | (3x/8)+1-(1x/8)=2+(5x/8)+(x/8) | | (15-9/2)^2 | | (r-6)2= | | d^2+16d+64=0 | | h(x)=-8x^3+14x-35 | | 6n-3=8n+7 | | 8a-1=2a+23 | | B=870(9+0.03) | | 6x+2+7=10 | | B=870(1+0.03)9 | | 8x-5=-29 | | 5(2x+4)=9x+5 | | B=870(1+0.03) | | 7x+2x=29 | | 3(x+4)-5=11 | | 7x+2+x=29 | | 8-2x=3x-67 | | 5x+4=3x+1+2x+3 | | (1/2x^2+5)^2 | | 3x+5x-8=0 | | 2(x-2)-1=5 | | 5m+4=3m-1+2m | | 133=x+9+3x | | 13x-9+2x-5=12x-1+2 | | 6x(6x)+4x=-10 | | q(5)=100-4*5 |